Identificação e quantificação de microrganismos em infecções periapicais crônicas pós-terapia endodôntica - Furtado, Wederson Tavares (2014)
For the control of infection in Endodontics, often not satisfactorily achieved perpetuating pathological processes after endodontic therapy, collected by endodontic surgery, the apex (hard tissue) and surrounding soft tissue of teeth with chronic periapical endodontic infections after therapy and we set out to identify and quantify three microorganisms Fusobacterium nucleatum, Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans these sites. The samples of soft tissue and hard tissue for each patient were packed separately ground by means of orthodontic pliers, had their genetic material extracted and subjected to the reaction method Polymerase Chain in Real Time by SYBR Green system. All patients (n = 30) had at least one microorganism in one of the two sites. F. nucleatum was the most microorganism present, 21 samples of soft tissue (70.0%) and 22 hard tissue (73.3%) also showing the highest average number of copies, 1.12E +06 for soft tissue and 1.33E +04 for hard tissue for each patient, followed by A. actinomycetemcomitans, which was present in 08 samples of soft tissue (26.6%) and 07 hard tissue (23.3%), with a mean copy number of 5.82 E +03 for soft tissue and 5.70E +02 for hard tissue. The lower prevalence and lower average number of copies were evaluated P. gingivalis identified in 04 specimens of soft tissue (13.3%) and hard tissue in 05 (16.6%) with 4.67E+02 and 6.00E +02 E +01, respectively. We conclude that the presence of microorganisms in endodontic post-treatment periapical lesions has been underestimated relative to both the presence and the bacterial species needing additional clarifications in order to be able to combat and neutralize periapical infection.